Effects of processing conditions on microstructure, electrical conductivity and mechanical properties of MWCNT/alumina composites prepared by flocculation. Issue 14 (November 2015) - Wang, Weili; Yamamoto, Go; Shirasu, Keiichi; Nozaka, Yo; Hashida, Toshiyuki
Abstract: MWCNT/alumina composites were prepared by a flocculation method combined with acid treatment of the MWCNTs and spark plasma sintering. The effects of varying the processing conditions, namely the acid treatment temperature (50–80 °C), MWCNT content (0–10 vol.%) and sintering temperature (1200–1600 °C) on the composites' microstructure, electrical conductivity and mechanical properties were investigated. This found that flocculation processing brings about a good dispersibility of the MWCNTs, especially with higher acid treatment temperature, which enhances their reinforcing and grain refining effect. When combined with a low sintering temperature, this significantly improves the mechanical properties of the composites.As a result, a composite prepared using a sintering temperature of 1200 °C and an acid treatment temperature of 80 °C exhibited a fracture toughness greater than that of a monolithic alumina, even with a MWCNT content as high as 10 vol.%.